Technical Entrepreneurship in Small Repairing Firms: A Study on Motorbike Repairing Workshops in Sylhet City (Journal of Business and Technology (Dhaka), 2014)
This research straightforwardly dilates the real scenario with an attempt to deal with all issues regarding motorbike workshops in Sylhet City, Bangladesh. Though analyzing the managerial activities appears as one of the core concerns of the research, it identifies the opportunities of entrepreneurial development for innovative and technically skilled persons. Through the observation of the formation and operational activities of such kind of workshops, the research attempts identifying problems faced by those firms, and eventually tries to produce solutions in that problem domain in the form of suggestions. The work has an endeavor to find out the historic pattern of the establishment of this kind of enterprise that helps understand whether the entrepreneurs are chronically affected by their families. The empirical study of the research also approaches to examine whether assistance from the government and NGOs to setup and to operate this type of entrepreneurship is required. DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18287 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013; 79-94